PENGARUH PEMBERIAN PUPUK GUANO DAN POC AIR CUCIAN BERAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis Sativus L) - Ahmad Supardi, Bimo; Usman; Armadi, Yukiman; Jafrizal; Habiburahman (Universitas Muhammadiyah Bengkulu, 2025)
Cucumber (Cucumis sativus L.) is a widely utilized plant in daily life, serving as a fresh vegetable, a base for pickles, juice, and even cosmetics. However, cucumber production in Indonesia has experienced a significant decline, partly due to the suboptimal availability of nutrients in the cultivation land. This study aims to explore the effects of guano organic fertilizer and rice wash water liquid organic fertilizer (POC) on the growth and yield of cucumber plants. The research was conducted in Bentiring Village, Bengkulu City, using a two-factor Randomized Block Design (RBD). The first factor was guano fertilizer with doses G0 (control), G1 (100 g/plant), G2 (200 g/plant), and G3 (300 g/plant), while the second factor was rice wash water POC with concentrations P0 (control), P1 (25 ml/L), P2 (50 ml/L), and P3 (75 ml/L). The analysis of variance revealed a significant interaction between guano fertilizer and rice wash water POC on various cucumber growth parameters, such as tendril length, number of leaves, number of fruits, fruit length, as well as fruit weight per plant and per plot. The best results were obtained from the combination of 300 g/plant of guano fertilizer and 75 ml/L of rice wash water POC, which produced a plot fruit weight of 2.01 kg. This study demonstrates that both types of fertilizers can improve the quality and quantity of cucumber yield, with rice wash water POC enhancing soil structure and increasing nutrient availability. Keywords: Cucumber, Guano fertilizer, Rice wash water POC